Shallow Carbonate for Underground Gas Storage in West Java, Indonesia - Edison Sirodj; Edy Sunardi; Billy G. Adhiperdana; Iyan Haryanto (Journal of Petroleum Science and Technology, 2020)
The Parigi Formation has been a significant gas exploration in West Java Basin. This is due to their abundance, and they occur at shallow depths (800-1000 m). The main objective of this study was to focus on the characteristics and distribution patterns of the shallow carbonate to be used for gas storage. The case will be focused on Parigi Formation as a reservoir carbonate in the depleted oil and gas field in West Java Basin. These build-ups are better developed in onshore West Java Basin, where they exhibit coral reef frameworks and reach over 450 m in thickness. Moreover, Parigi Formation carbonate is well exposed in Palimanan, West of Cirebon City, and it is divided into four types of lithofacies. Preservation conditions, storage capacity, effective injection, and production are important factors in underground gas storage. In the geological site, factors that need to be evaluated are as follows: a reservoir, trap sealing, and tectonic activities in the surrounding area. However, in the USA and Europe, the porous reservoir formations such as sandstone or carbonate at depths of 500 - 1800 meters are common in storing natural gas in large volumes size. Ultimately, according to this case study, it has been found out that the most influential parameters for storing natural gas are porosity and permeability (petrophysical properties).